2014
DOI: 10.32637/orli.v44i1.81
|View full text |Cite
|
Sign up to set email alerts
|

Korelasi positif ekspresi cyclooxygenase-2 dengan microvessel density pada karsinoma nasofaring

Abstract: Pendahuluan: Tumor memerlukan proses pembentukan pembuluh darah baru untuk tumbuh dan bermetastasis yang dikenal sebagai proses angiogenesis. Angiogenesis dapat dinilai secara imunohistokimia dengan Microvessel Density (MVD). Proses angiogenesis dapat dipicu oleh berbagai faktor angiogenik. Beberapa penelitian menemukan ekspresi Cyclooxygenase-2 (COX-2) meningkat pada kanker. COX-2 dapat merangsang pengeluaran faktor-faktor angiogenik. Pada penelitian ini akan dilihat apakah angiogenesis, yang dinilai dengan M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
3
1
0
Order By: Relevance
“…Initial stages were found in 9 subjects (13.8%) and advanced stages as many as 56 subjects (86.2%). This result is in correspond with Hasibuan et al (2014), whose obtain 62.5% subjects with stage IV NPC and none stage I NPC [7]. Study in Europe obtain as many as 39.1% of early stage NPC and 60.9% of late stage NPC [8].…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Initial stages were found in 9 subjects (13.8%) and advanced stages as many as 56 subjects (86.2%). This result is in correspond with Hasibuan et al (2014), whose obtain 62.5% subjects with stage IV NPC and none stage I NPC [7]. Study in Europe obtain as many as 39.1% of early stage NPC and 60.9% of late stage NPC [8].…”
Section: Resultssupporting
confidence: 89%
“…The distribution of subjects based on the clinical stage of undifferentiated type NPC in the Balinese was an early stage as many as 9 subjects (13.8%) and an advanced stage as many as 56 subjects (86.2%). This is in accordance with several studies such as Hasibuan et al as many as 62.5% of patients with stage IV NPC and no patient in stage I [7]. Research in Europe found 39.1% of patients with early-stage NPC and 60.9% of patients with advanced-stage [7].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Misdiagnosis often results from a lack of knowledge about the early signs and symptoms of nasopharyngeal carcinoma [1]. Therefore, early symptoms of NPC are often overlooked and patients are diagnosed after the size of the tumor and enlarged lymph nodes are large at an advanced stage so that patients often come for treatment when they are at an advanced stage [14].…”
Section: Discussionmentioning
confidence: 99%